Analisis Vegetasi dan Potensi Hutan Bukan Kayu di Kawasan Hutan Kampung Pagai, Distrik Airu, Kabupaten Jayapura, Papua - Rosye H.R. Tanjung; Suharno suharno; Jhon D. Kalor (Jurnal Biologi Papua, 2012)
Forest is a resources system which has prospective materials to be used for human needs. Local people within everyday life are very dependent on the natural surroundings, as well as the use of nature for human needs tend to increase. The purpose of this research is to do the analysis of vegetation and determine the potential use of non-timber forest products in Kampung Pagai, Airu District, Jayapura. The method used for the analysis of vegetation is the square plot, while the method to figure out the potential of non-timber forest adopts the method developed by Waluyo (2004). The results showed that there are at least 39 species of trees belonging to the 26 families. Regeneration of trees showed the condition which is good based on the diversity of tree species in the Sapling level, especially matoa (Pometia pinnata), kayu besi (Instia bijuga), and various plants of Ficus ssp. The potential uses of non-timber forest are also quite high. Several types of plants can be used as building materials and accessories, medicines, ornaments (including orchids), fruits, and vegetables. Key words: forest, vegetation, non-timber forest product, Airu District, Jayapura.